2016
DOI: 10.5194/isprs-archives-xli-b8-379-2016
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Application of the Geophysical Changes in the Coastlines and Rivers of Zambales, Philippines

Abstract: ABSTRACT:Geophysical changes in river outlet, river upstream and coastlines near the rivers of Bucao and Santo Tomas in Zambales, Philippines were analyzed using the Google Earth's historical satellite imageries from 2004 to 2013. Data in 2015 were gathered from in situ field measurements ground validation. The study aimed to measure and determine changes in the width of river outlet, width of river bank upstream and shifting of coastline.Results revealed that there was a decrease and increase in the width siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Taking examples from across the Philippines, remote sensing analyses have indicated the dynamic planform morphologies of selected rivers. Reach-scale aerial imagery analysis in the Bucao and Santo Tomas Rivers (Zambales) showed spatially variable changes in river width between 2004 and 2013; a legacy effect of sediment supply from the Mt Pinatubo volcanic eruption in 1991 (Paz-Alberto et al 2016). A national-scale assessment of river migration in the vicinity of 74 large river bridges using Landsat satellite imagery showed that some river reaches have remained approximately stable over the 30-year monitoring period whilst others have considerably adjusted through migration, contraction and expansion (Boothroyd et al 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Taking examples from across the Philippines, remote sensing analyses have indicated the dynamic planform morphologies of selected rivers. Reach-scale aerial imagery analysis in the Bucao and Santo Tomas Rivers (Zambales) showed spatially variable changes in river width between 2004 and 2013; a legacy effect of sediment supply from the Mt Pinatubo volcanic eruption in 1991 (Paz-Alberto et al 2016). A national-scale assessment of river migration in the vicinity of 74 large river bridges using Landsat satellite imagery showed that some river reaches have remained approximately stable over the 30-year monitoring period whilst others have considerably adjusted through migration, contraction and expansion (Boothroyd et al 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Torrential and intense rainfall, severe storm occurrences and strong typhoons have occurred and being experienced which caused massive landslides and excessive flooding in various parts of the country [3] [4] [5] [6]. It was also during the past 15 years that the Philippines was hit by the strongest typhoon ever recorded, the most destructive, the deadliest, and that registered the highest recorded 24-hour rainfall [3].…”
Section: Introductionmentioning
confidence: 99%